Ectopic transcription due to inherited histone methylation may interfere with the ongoing function of differentiated neurons - Juan D. Rodriguez; Monica N. Reeves; Sindy R. Chavez; Hsiao-Lin V. Wang; Jaely Z. Chavez; Rhea Rastogi; Liyang I. Sun; Mackenzie S. Roberson; Elicia A. Preston; Zaynab Massenburg; Kiani N. Cruz; Madhav S. Chadha; et al. (Proceedings of the National Academy of Sciences, 2025)
How mutations in histone modifying enzymes lead to neurodevelopmental defects is unknown. To address this question, we took advantage of the invariant embryonic lineage and adult nervous system in Caenorhabditis elegans to investigate a double mutant between spr-5/Lsd1/Kdm1a (H3K4me1/2 demethylase) and met-2/Setdb1/Kmt1e (H3K9 methyltransferase). We demonstrate that spr-5; met-2 double mutant worms have a severe chemotaxis defect caused by the ectopic expression of germline genes in somatic tissues. Despite this behavioral defect, we observe few embryonic lineage alterations and the normal complement of neurons. This raised the possibility that the abnormal chemotaxis behavior may be due to ongoing defects in terminally differentiated cells rather than alterations in development. Consistent with this possibility, we find that shutting off the ectopic expression of germline genes specifically in neurons rescues chemotaxis in spr-5; met-2 mutants. Remarkably, shutting off the ectopic germline expression in spr-5; met-2 adult worms, that had a chemotaxis defect earlier in development, is also sufficient to rescue chemotaxis behavior. These results suggest that ongoing inappropriate transcription in neurons can block normal behavior despite the chemotaxis neurons being intact.